Jurnalisme sebagai Arena Pertarungan Kepentingan: Telaah Teori Kebudayaan - Amirudin Amirudin (Program Studi Sastra Indonesia, Fakultas Ilmu Budaya, Universitas Diponegoro, 2018)
This paper is a theoretical study of the use of cultural theory which played to explain journalism activities that just not an activity to provide accurate information in the public space. In an industrial context, in fact journalism activities has face any complex situasion. Now, the activities is no longer exclusively owned by journalists, but journalism is a kind of football arena that have some interest in it. To present news, journalists must be able to absorb various interest from various trajectories. There is a game metaphor that journalists must follow, and how journalist do